Energy consumption when working the shock-separator measurer - Serdyuk, V; Rudenko, V; Zubko, V (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes)
The energy costs and the process of grain grinding during the operation of the shock-crusher are investigated in order to increase its efficiency and reduce energy consumption. The technological and design factors that most influence both energy consumption and the degree of grain grinding are identified. The experiments were conducted on a pilot plant designed and manufactured in the laboratory. Technological and design factors most influencing the research parameters and accepted for further experiments: the angle of inclination of the reflector plates of the stator; linear speed (speed) of the rotor; grain supply; clearance between rotor and stator. The accepted factors meet certain requirements: they are independent variables and are measured with sufficient accuracy by available means; are unambiguous and manageable; compatible with each other; are quantified and are not correlated with linear correlation relationships. The experiments were conducted on a pilot plant designed and manufactured in the laboratory.A fully factorial experiment showed that it is not possible to describe a linear energy flow model and the degree of grain grinding with the required accuracy. Therefore, the experiments were continued and "star" and "zero" points were added to the full factorial design of the experiment, which transformed the planning matrix into a second order rotatable plan. The results of studies show that the angular velocity of the rotor, the increase of which leads to a rapid increase in the used power, has the greatest influence on the energy consumption during the operation of the shredder. The degree of grinding of the grain is most influenced by the angular velocity of the rotor and the angles of inclination of the reflector plates of the stator. To analyze the influence of individual factors on energy consumption and the degree of grain grinding, we construct conditionally one-dimensional dependencies, stabilizing the value of other factors at a certain level. By changing the studied factors, it is possible to select the most energy-saving mode of operation of the shredder with the desired specified grain grinding module.